Great Britain autographs collection
Miscellaneous autograph letters, legal and financial documents, printed material, cut signatures, fragments, and other papers with signatures of British statesmen and members of the nobility, including Queen Victoria and Prince Albert, Arthur Capel, 1st Earl of Essex, Sir John Fielding, Sidney Godolphin, 1st Earl of Godolphin, Frederick North, 2d Earl of Guilford, and Henry Pelham. Includes printed list (157 pages) of 18th century Royal Regiment of Artillery officers, Marine Forces, Land Forces, Horse Guards, Dragoons, and Engineers.
Collection material in English.
Keywords: Victoria, -- Queen of Great Britain, -- 1819-1901 -- Autographs; Albert, -- Prince Consort, consort of Victoria, Queen of Great Britain, -- 1819-1861 -- Autographs; Godolphin, Sidney Godolphin, -- Earl of, -- 1645-1712 -- Autographs; Essex, Arthur Capel, -- Earl of, -- 1631-1683 -- Autographs; North, Frederick, -- Lord, -- 1732-1792 -- Autographs; Fielding, John, -- Sir, -- 1721-1780 -- Autographs; Pelham, Henry, -- 1695?-1754 -- Autographs; Great Britain. -- Army -- Officers -- Autographs; Statesmen -- Great Britain -- Autographs